Evaluation of patient satisfaction of the status of appointment scheduling systems in outpatient clinics: Identifying patients' needs - Mohammad Reza Mazaheri Habibi; Fahimeh Mohammad Abadi; Hamed Tabesh; Hasan Vakili-Arki; Ameen Abu-Hanna; Saeid Eslami (Wolters Kluwer Medknow Publications, 2018)
Appointment scheduling systems are potentially useful tools for enhancing the patient satisfaction. This study was conducted to inspect patient's needs and satisfaction of the current status of appointment scheduling systems in outpatient clinics. This cross-sectional study was conducted in 10 outpatient clinics with different specializations. The outpatient clinics were selected based on the stratified randomization method. Data were collected using a questionnaire from December 2016 to March 2017. The questionnaire reliability was measured with the participation of 15 patients using the test-retest method. The content validity was also evaluated by 13 experts. A total of 319 patients completed the survey. The mean score of overall patient satisfaction and the patient satisfaction of the clinic environment were 6.73 ± 0.16 and 8.30 ± 0.12, respectively. The average waiting time was 64.2 ± 3.45 min. The service time took on an average 9.85 ± 0.37 min. The patient satisfaction of the clinic environment (P = 0.023), length of waiting time (P = 0.001), and duration of service time (P = 0.005) had a statistically significant association with overall patient satisfaction. Based on the results, the need for improving overall patient satisfaction score was felt. The patient satisfaction of waiting time, service time, and clinic environment had the greatest influence on overall patient satisfaction. Furthermore, it is recommended that a web-based appointment scheduling system should be implemented.